Representations of Human Domination in Climate Policy Documents: A Transitivity Analysis - Yahya, Mad; Roselani, Ni Gusti Ayu (English Language Education, Universitas Internasional Batam, 2024)
This research aims to analyse the transitivity system of Pembangunan Berketahanan Iklim (PBI) documents, one of the key climate governance policy documents in Indonesia, based on an ecolinguistic approach. Using Halliday’s transitivity system (2014), researchers explore clues to the world experience of policymakers in positioning the relationship between humans and their environment through language features in texts. Also employing the same transitivity system, this research applies a mixed-method, integrating both qualitative and quantitative techniques to provide a comprehensive analysis. The authors utilized AntConc 4.2.2. to analyse the corpus of 46,789 tokens. Concordances containing keywords: lingkungan, alam, habitat, ekosistem, and hayati were analyzed using the transitivity system framework to identify the distribution of process types and participant roles within the corpus. Research findings show a significant prevalence of material processes, indicating a focus on actions and events. Furthermore, the analysis shows the patterns of the active roles of human participants, actor obscuring, as well as environmental keywords that fill the role of passive participants and circumstantial phrases that clarify the tradition of human domination over the environment. These transitivity patterns indicate stylistic features of an ambivalent discourse that perpetuates human domination over the environment. From the perspective of Living! ecosophy (Stibbe, 2021), language patterns that still represent anthropocentric perspectives are incompatible with sustainable ecological discourse. This research of transitivity analysis enriches the study of climate governance discourse in policy documents in the Indonesian context.